(Un)bounded rationality in decision making and game theory: Back to square one? - Werner Güth; Hartmut Kliemt (Games, 2010)
Game and decision theory start from rather strong premises. Preferences, represented by utilities, beliefs represented by probabilities, common knowledge and symmetric rationality as background assumptions are treated as 'given.' A richer language enabling us to capture the process leading to what is 'given' seems superior to the stenography of decision making in terms of utility cum probability. However, similar to traditional rational choice modeling, boundedly rational choice modeling, as outlined here, is far from being a 'global' theory with empirical content; rather it serves as a tool to formulate 'local' theories with empirical content.
Keywords: C70; B40; A12; 330; bounded rationality; methodology of decision; game theory